Dominasi Patriarki dalam Film Yuni: Kajian Perspektif Cultural Studies - Irfan Zaidan Hidayat; Nabilal Alamin; Rifma Ghulam Dzaljad (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the practices of patriarchal domination in Yuni, a film directed by Kamila Andini, using Stuart Hall's Cultural Studies perspective. As a form of mass communication, film functions not only as entertainment but also as a medium for producing meanings that shape ideology, power relations, and social realities within society. This research employs a critical paradigm with a descriptive qualitative approach. The data were collected through observations of five selected scenes using purposive sampling based on the presence of patriarchal domination practices. The selected scenes were analyzed by examining dialogues, characters’ expressions, visual symbols, and the social context using Stuart Hall’s Cultural Studies framework. The findings reveal that patriarchal domination in Yuni is manifested in four major forms: ideological domination that positions marriage as the primary goal for women, social control over women who challenge patriarchal norms, the subordination of women in decision-making processes, and restrictions on women’s access to education. The analysis further demonstrates that these forms of domination are maintained through the continuous production and reproduction of cultural meanings by families, social environments, and societal norms, causing patriarchal values to be perceived as natural and legitimate. At the same time, the character of Yuni demonstrates resistance by defending her right to pursue higher education and determine her own future. Therefore, Yuni not only critiques patriarchal culture but also offers an alternative discourse on gender equality and women’s autonomy in shaping their own lives.